The Role of Language Environment in Developing Speaking Skills Based on Skinner's Behavior Theory for Students of Ma'had Hidayatullah Al-'Ali Batu - Muhammad Sirojuddin Iqbal Sukadi; Abdul Aziz; Nur Ila Ifawati (Insitut Muslim Cendekia, 2025)
This study aims to reveal the role of the language environment in developing students’ speaking skills at Ma’had Hidayatullah Batu, using Skinner’s behaviorist theory as the theoretical framework. The researcher employed a qualitative case study approach, with data collected through observation, interviews, and documentation involving lecturers, students, and several institutional records. Data were analyzed using Miles and Huberman’s model through the stages of data reduction, data display, and conclusion drawing. To enhance the credibility of the findings, triangulation was applied. The results indicate that the language environment at Ma’had Hidayatullah Batu effectively contributes to the development of speaking skills through various activities such as daily conversations, drama performances, debates, wall magazines, and speech competitions. These activities were designed based on the principles of behaviorist theory, including practice, repetition, and positive reinforcement.